The role of Mek/Erk signalling inhibition and Krüppel-like factor 2 in mouse ground state pluripotency - Yeo, Jia Chi (2015)
The maintenance of undifferentiated mouse embryonic stem cells (mESCs) requires the presence of LIF and serum. Interestingly, by using two chemical molecules to inhibit both the pro-differentiative Fgf/Mek/Erk and Gsk3/Tcf3 pathways in mESCs (dual inhibition or “2i”), a pluripotent “ground state”, resembling the mouse pre-implantation epiblast can be established without the need for LIF and serum. While Gsk3-inhibition is known to alleviate Tcf3-mediated repression of Esrrb, the molecular mechanism downstream of Mek/Erk inhibition remains to be identified. Here, it was uncovered that Erk2 phosphorylates the Krüppel-like factor 2 (Klf2), leading to Klf2 proteasomal degradation. Mek/Erk inhibition during 2i conditions thus serves to halt Klf2 phospho-degradation, leading to Klf2 protein stabilisation and maintenance of ground state pluripotency. Indeed, while Klf2-null mESCs are viable under LIF/Serum, they undergo apoptosis during 2i culture. Additionally, it was found that Klf2 overexpression is sufficient to replace Mek-inhibition, allowing for mESC self-renewal under Gsk3-inhibition alone. Taken together, this study highlights the importance of Klf2 during 2i conditions, and defines the Mek/Erk/Klf2 pathway with the Gsk3/Tcf3/Esrrb axis to establish ground state pluripotency.